2018
DOI: 10.1002/app.46822
|View full text |Cite
|
Sign up to set email alerts
|

Migration and performance of erucamide slip additive in high‐density polyethylene bottle caps

Abstract: Diffusion of erucamide and their morphology on surface characteristics of high-density polyethylene (HDPE) screw caps depend on storage conditions. Erucamide performance relies on its amount, distribution, and consistency on the surface of HDPE. Specific application and removal torques can be achieved by controlling the amount of erucamide on the surface. The surface amount and the torque increased to an optimum level at 38 and 50 C within 120 hours of incubation, while they remained unchanged for lower temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…The results suggested that erucamide formed stratified surface layers with the hydrophobic chains oriented outwards, responsible for lower surface wettability. In a follow-up study, Dulal et al [16] further showed three growth stages of the slip additive surface layer: starting with a discontinuous monolayer, developing to form bilayers and finally multilayers. In all cases, the erucamide molecules were presumed oriented with the hydrocarbon chains pointing outwards, whilst the surface layer was not well-ordered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggested that erucamide formed stratified surface layers with the hydrophobic chains oriented outwards, responsible for lower surface wettability. In a follow-up study, Dulal et al [16] further showed three growth stages of the slip additive surface layer: starting with a discontinuous monolayer, developing to form bilayers and finally multilayers. In all cases, the erucamide molecules were presumed oriented with the hydrocarbon chains pointing outwards, whilst the surface layer was not well-ordered.…”
Section: Introductionmentioning
confidence: 99%
“…Erucamide (13-cis-docosenamide, C22H43NO; Figure 1) is one of the most widely used fatty acid amide slip additives in polyolefin manufacturing [9,11,12,[14][15][16], reportedly reducing the coefficient of friction (CoF) down to 0.2 [9,17]. Its stability, low toxicity and transparency, along with its extraordinary slip properties attainable at low concentrations, find erucamide used as an antifouling [18], antifogging [19], angiogenic [20,21], antiviral [22], dispersing [23][24][25][26], or scratch resistant [27][28][29] agent in a wide spectrum of applications ranging from food packaging, automobile and textile industries to hygiene and healthcare products.…”
Section: Introductionmentioning
confidence: 99%
“…Amphiphilic molecules such as alkyl derivatives (e.g., fatty acids, fatty amines, and fatty acid amides) are widely used to tune interfacial functionality without interfering with substrate bulk properties of materials ranging from polymers (i.e., polyethylene (PE), polypropylene (PP)), and metal surfaces (i.e., iron oxide, steel) to model substrates (i.e., silica, mica, graphite). These surface-active molecules are often used in order to moderate material friction and adhesion properties providing easier handling, processing and frequently superior consumer perception of the final product. The self-assembly of amphiphilic molecules (i.e., film thickness, packing density, and molecular orientation) is highly dependent on their molecular architecture (head group chemistry, , alkyl chain length, and degree of unsaturation ,, ) and can be controlled with the additive concentration, substrate chemistry, and sample preparation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Erucamide (13- cis -docosenamide, C 22 H 43 NO; Figure L) is a common slip additive for controlling frictional and adhesive properties for polymer materials and facilitating their production consistency (e.g., handling and manufacturing) and superior consumer perceptions of the final product (e.g., softness, general appearance). , Erucamide can be introduced to the material externally through physical adsorption or internally via the “ blooming ” process during which erucamide molecules migrate through the polymer matrix as a result of their incompatibility with the hydrophobic polyolefin. Both methods result in surfaces of erucamide-modified morphology and nanomechanical properties (i.e., friction and adhesion) tunable with substrate materials, ,,,, erucamide concentration, , and temperature. The molecular packing and orientation of erucamide, particularly in the outermost layer of an erucamide thin film, is highly relevant to its nanomechanical properties and performance to tailor surface properties of polymer products.…”
Section: Introductionmentioning
confidence: 99%
“…When the ejection is completed, the threads recover their initial shape, without any residual deformation remaining on the caps. If the screw caps were not fabricated from a highly flexible polymeric material, breakage of undercuts and ridges of the threading would ultimately occur, [ 5 ] thus determining the scrap of the part. On the other side, if the screw caps would not be extracted by the so‐called “torn‐off” mechanism, the cycle time of the caps manufacturing process would increase that much and the final cost of the caps would augment considerably, thus causing the loss of competitiveness of the whole production process.…”
Section: Introductionmentioning
confidence: 99%